The Fermi Galactic Center GeV Excess and Implications for Dark Matter - Ackermann, Markus; Ajello, Marco; Albert, A.; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2017)
The region around the Galactic Center (GC) is now well established to be brighter at energies of a few GeV than what is expected from conventional models of diffuse gamma-ray emission and catalogs of known gamma-ray sources. We study the GeV excess using 6.5 yr of data from the Fermi Large Area Telescope. We characterize the uncertainty of the GC excess spectrum and morphology due to uncertainties in cosmic-ray source distributions and propagation, uncertainties in the distribution of interstellar gas in the Milky Way, and uncertainties due to a potential contribution from the Fermi bubbles. We also evaluate uncertainties in the excess properties due to resolved point sources of gamma rays. The GC is of particular interest, as it would be expected to have the brightest signal from annihilation of weakly interacting massive dark matter (DM) particles. However, control regions along the Galactic plane, where a DM signal is not expected, show excesses of similar amplitude relative to the local background. Based on the magnitude of the systematic uncertainties, we conservatively report upper limits for the annihilation cross-section as a function of particle mass and annihilation channel.
CRIS-Team WoS Importer:2020-01-15